Propuesta del gestión de costo para los proyectos de la Constructora Hermanos Brenes S.A. - Blanco-Brenes, Luis Felipe (Instituto Tecnológico de Costa Rica, 2016)
The work presented below, is the development of a proposal for cost control processes Doña Blanca condominium infrastructure of its first stage, developed by the company Constructora Hermanos Brenes S.A The main objective developed was to create a methodology of cost control, from a successful creation of the budget and proper control of each of the construction processes to further deploy bases analyzable data for improved plan costs. To this end we investigated on procedures used in other departments in the company of how costs are managed. So also he was asked about how they have managed to control project costs of urbanization. Some problems encountered such as better project schedule, lack of instructional, communication and unforeseen situations were causes that during the investigation did not allow the work will be developed as planned. With cost control that fits the way you work in construction, hand communication and teamwork, it is possible to achieve the success of the project and future similar works.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Control; Contrucción; Presupuesto; Riesgos; Procesos